IoT centralized support system construction strategy oriented connected - Zhao DONG; Lei QI; Huiqiong GU; Hao ZHU; Xu CHEN (Dianxin kexue)
To implement the “connected” strategy of telecom operators,the construction strategy of IoT centralized support system,as the core of the network connection management,is becoming a difficult problem to be discussed.The demands of business development and evolution of network architecture were elaborated.The technical architecture and function architecture of IoT centralized support system were defined.The implementation and developmentstrategies of centralized support and large connected support were discussed.